RANCANG BANGUN SIMULASI PEMANFAATAN METODE INTERLOCK PROTOCOL UNTUK MENGATASI MAN-IN-THE-MIDDLE-ATTACK BERBASIS DEKSTOP - Rudi Syah Putra (UPPM, 2020)
In the process of data communication, even though the data has been encrypted, there is a possibilitythat the data can be known by others. One possibility is that the person intercepted thecommunication media used by the two people who were communicating. This is what is called manin-the-middle-attack.Thisman-in-the-middle-attackproblemcanbepreventedbyusingtheinterlockprotocol.ThisinterlockprotocolwascreatedbyRonRivestandAdiShamir.Thecorealgorithmofthis protocol is that it sends 2 encrypted messages. The first part can be the result of the one wayhash function of the message and the second part is the encrypted message itself. This causes theintercepting person to be unable to decrypt the first message using his private key. He can only createa new message and send it to the person who will receive the message.